The Winner's Curse and Public Information in Common Value Auctions - Kagel, John H.; Levin, Dan (American Economic Review, 1986)
Experienced bidders show sensitivity to the strategic considerations underlying common value auctions, but not to item valuation considerations. Auctions with large numbers of bidders (6-7) produce more aggressive bidding than with small numbers (3-4), resulting in negative profits, the winner's curse. Providing public information about the value of the item increases seller revenue in the absence of a winner's curse, but produces the contrary result in its presence.